Pseudothrombocytopenia observed with ethylene diamine tetra acetate and citrate anticoagulants, resolved using 37°C incubation and Kanamycin - Vandana Kamath; Parimal Sarda; Mary Purna Chacko; Usha Sitaram (Wolters Kluwer Medknow Publications, 2013)
Pseudothrombocytopenia (PTP) is defined by falsely low platelet counts on automated analyzers caused by in vitro phenomena including large platelet aggregates in blood samples. Diagnosis and resolution of PTP is crucial as it can lead to unwarranted interventions. We discuss a case of PTP in a pre-surgical setting, which was resolved using 37°C incubation and Kanamycin.